Emotional Compatibility and the Effectiveness of Antidrinking Messages: A Defensive Processing Perspective on Shame and Guilt - Agrawal, Nidhi; Duhachek, Adam (Journal of Marketing Research, 2010)
Five studies examine how the two distinct emotional states of shame and guilt influence the effectiveness of messages that highlight socially undesirable consequences of alcohol consumption. Appeals that frame others as observing versus suffering the negative consequences of binge drinking differentially activate shame and guilt. Given these emotional consequences of message framing, the authors examine the interaction between incidental shame or guilt and message framing on drinking intentions and behavior. Compatible appeals (i.e., appeals that elicit the same emotion as being incidentally experienced by the consumer) are less effective in influencing behavioral intentions and beverage consumption because of a process in which consumers discount the notion that they may cause the negative consequences outlined in the message. Such defensive processing of compatible messages is driven by a desire to reduce the existing negative emotion.